The conceptualisation of work integrated learning practices in hospitality education to develop students' career preparedness: a preliminary paper / Faezanuurfarhha Md Yusof, Muhammad Majid, Ahmad Syahmi Fadzil and Mohamad Faizal Ramli - Md Yusof, Faezanuurfarhha; Majid, Muhammad; Fadzil, Ahmad Syahmi; Ramli, Mohamad Faizal (UiTM Cawangan Johor, 2025)
The un1t1illingness of hospitality graduates to 1t1ork in this industry after graduation has 1t1orsened the labour shortage issue in Malaysian hospitality sector. Collaboration between higher education institutions and industry players through it work integrated learning (WIL) is critical for bridging theoretical knowledge and real-it world application in the hospitality sector, thereby improving students' learning processes. Including WIL in the curriculum can help students prepare for their future careers, improve employability skills, and gain a rational understanding of knowledge 1 through the practice of 'action'. This article analyses the effectiveness of WIL practices in hospitality institutions by using survey research design to collect data from hospitality graduates, as 1t1ell as semi-structured intervie1t1 from graduates, institutions and industry partners in Johor and Klang Valley, Malaysia to meet the current needs of hospitality sector. Particular attention should be focused on enhancing students' self efficacy, engagement, and satisfaction in WIL activities to increase their enthusiasm for pursuing careers in the hospitality sector. Therefore, upcoming hospitality programmes bought to thoughtfully integrate WIL into the curriculum, considering the needs of the industry and the career development pathways of graduates.